Multistring seven-level quasi Z-source based asymmetrical inverter - Ramesh Rahul Jammy; Kirubakaran Annamalai (Institute of Advanced Engineering and Science, 2019)
In this paper, a single-phase multistring seven-level Quasi-Z-source based Asymmetrical Inverter suitable for grid-connected photovoltaic (PV) system is presented. This topology is an upgrade of quasi-Z-source dc-dc (qZs) network and Asymmetrical multilevel inverter (AMLI). The AMLI generates higher number of levels with reduced switch count and number of sources when compared to symmetrical cascaded based MLI. The qZs network acts as an intermediate stage between the low-voltage PV array and AMLI, to enhance the output voltage gain of the inverter. The steady state performance the topology is verified through MATLAB simulation and experimentation. A laboratory prototype model is developed for a capacity of 200W to validate the theoretical studies. Finally, a comparative assessment of the proposed with the existing topologies is presented.